Effect of vitamin C on neutrophil function after high-intensity exercise - Krause, R.; Patruta, S.; Daxböck, F.; Fladerer, P.; Biegelmayer, C.; Wenisch, C. (European Journal of Clinical Investigation, 2001)
High-intensity exercise leads to an increased risk of upper respiratory tract infections in athletes, which had been related to an exercise-induced impairment of neutrophil function. In this study, several indices of neutrophil function were analysed before and after a biathlon and the effect of oral vitamin C on neutrophil function was determined.